Approaches in sensor-based system data modelling: a survey - Zailan, Muhd Amirul Hakim; Ishak, Iskandar; Sidi, Fatimah; Perumal, Thinagaran (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
Internet of Things (IoT) is a new technology live that helps to improve our everyday life by offering new services. Through IoT, recent developed technologies exist such as Big Data, Cloud Computing and Monitoring. Several approaches have been proposed in literature to reduce energy consumption and reduce communication overhead in sensor-based system such as Wireless Sensor Network (WSN). To optimize WSN, data aggregation is needed to secured data transmission at both sensor nodes and base station. In WSN, data aggregation process should be optimized in an energy efficient manner and providing quality data for processing is a challenge as sensor based system has smaller specification of hardware and software compared to bigger machines. In this paper, we reviewed all of the methods that have been proposed to model data on sensor-based systems. We also discussed the strengths and issues of each approaches.